Vascular complications following 1500 consecutive living and cadaveric donor renal transplantations: A single center study - Salehipour Mehdi; Salahi Heshmatollah; Jalaeian Hamed; Bahador Ali; Nikeghbalian Saman; Barzideh Ehsan; Ariafar Ali; Malek-Hosseini Seyed (Saudi Journal of Kidney Diseases and Transplantation, 2009)
The aim of this study was to document vascular complications that occurred fol-lowing cadaveric and living donor kidney transplants in order to assess the overall incidence of these complications at our center as well as to identify possible risk factors. In a retrospective cohort study, 1500 consecutive renal transplant recipients who received a living or cadaveric donor kidney between December 1988 and July 2006 were evaluated. The study was performed at the Nemazee Hospital, Shiraz, Iran. The assessment of the anatomy and number of renal arteries as well as the incidence of vascular complications was made by color doppler ultrasonography, angiography, and/or surgical exploration. Clinically apparent vascular complications were seen in 8.86% of all study patients (n = 133) with the most frequent being hemorrhage (n = 91; 6.1%) followed by allo-graft renal artery stenosis (n = 26; 1.7%), renal artery thrombosis (n = 9; 0.6%), and renal vein thrombosis (n = 7; 0.5%). Vascular complications were more frequent in recipients of cadaveric organs than recipients of allografts from living donors (12.5% vs. 7.97%; P= 0.017). The occurrence of vascular complications was significantly more frequent among recipients of renal allografts with multiple arteries when compared with recipients of kidneys with single artery (12.3% vs. 8.2%; P= 0.033). The same was true to venous complications as well (25.4% vs. 8.2%; P< 0.001). Our study shows that vascular complications were more frequent in allografts with multiple renal blood vessels. Also, the complications were much less frequent in recipients of living donor transplants.